2008
DOI: 10.1007/s10038-008-0315-x
|View full text |Cite
|
Sign up to set email alerts
|

RET polymorphisms and the risk of Hirschsprung’s disease in a Chinese population

Abstract: Hirschsprung's disease (HSCR) is a congenital disorder characterized by intestinal obstructions due to the absence of enteric ganglia along variable lengths of the intestinal tract. RET coding mutations have been found in approximately 50% of familial cases, but they only explain a minority of sporadic cases. Here, we report our investigation of a possible role of RET non-coding mutations in sporadic HSCR patients. The haplotypes of seven single nucleotide polymorphisms (SNPs), all located in a region 4 kb ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Liu CP et al reported C135 G/A and C1296 A/G at exon 2 and the combination of AG of these two SNPs were associated with susceptibility of HSCR in Southeast Chinese population [17,18]. Also, they observed these two SNPs were in LD with two other coding SNPs at exon 14 and exon 15 in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…Liu CP et al reported C135 G/A and C1296 A/G at exon 2 and the combination of AG of these two SNPs were associated with susceptibility of HSCR in Southeast Chinese population [17,18]. Also, they observed these two SNPs were in LD with two other coding SNPs at exon 14 and exon 15 in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a genome‐wide association study (GWAS) has revealed that a new candidate gene of NRG1 is associated with the risk of HSCR . Genetic associations of the single nucleotide polymorphisms (SNPs) in known susceptibility genes (such as rs2435357 and rs2505535 in RET , and rs2439305 in NRG1 ) were replicated in a number of studies . More recently, in our prior GWAS in a Korean population to discover new genetic loci in HSCR, vesicle‐associated membrane protein 5 ( VAMP5 ) was identified as a potential risk factor for the TCA subgroup of HSCR patients with a significance of p = 8.03 × 10 −5 at rs1254900 …”
Section: Introductionmentioning
confidence: 99%
“…9 Genetic associations of the single nucleotide polymorphisms (SNPs) in known susceptibility genes (such as rs2435357 and rs2505535 in RET, and rs2439305 in NRG1) were replicated in a number of studies. [10][11][12][13] More recently, in our prior GWAS in a Korean population to discover new genetic loci in HSCR, vesicle-associated membrane protein 5 (VAMP5) was identified as a potential risk factor for the TCA subgroup of HSCR patients with a significance of p = 8.03 9 10 À5 at rs1254900. 14 VAMP5 encodes synaptobrevin (a member of the SNARE protein complex), and its family has been reported to participate in the synaptic vesicle fusion process of ENS neurotransmission.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of heterozygous haploid in developing HSCR was 2 times higher than the normal population and 20 times higher than the homozygous haploid. In our analysis of the RET intron in the Chinese population with HSCR, we found that a high transmission frequency of the RET +3: T allele led to an increased susceptibility to HSCR (Zhang et al, 2007; Liu et al, 2008). A 5.7‐fold and 2.1‐fold increase in susceptibility to HSCR in males and females, respectively, was estimated in SNP haplotypes of the RET +3.…”
Section: Major Hscr Susceptibility Genesmentioning
confidence: 91%
“…We also found that the distribution of some other polymorphisms in the intron 1 was significantly different between cases and controls. Among these, two haplotypes were significantly associated with HSCR (Liu et al, 2008). Emison et al studied 882 probands with HSCR and 1478 first‐degree relatives from the US, European, and Chinese families and found that common mutations, individually and together, may contribute to the risk of HSCR.…”
Section: Major Hscr Susceptibility Genesmentioning
confidence: 99%